A Study of Inputs of Materials and Labour in Construction of Buildings and Roads - Planning Commission (Planning Commission Government of India, 1957)
The study by the Perspective Planning Division of the Planning Commission (December 1957) analyzes inputs of materials and labour in the construction of buildings and roads in India. Using data from the Central Public Works Department, the report establishes technical ratios for key building materials—such as cement, steel, bricks, and timber—and standardizes labour requirements per unit area and per monetary expenditure. Findings reveal that material costs account for 54–58% of building expenditures, with labour comprising approximately 25%, while road construction shows high material costs for aggregates and bitumen. The report also introduces a classification scheme for construction projects to facilitate consistent analysis. Overall, the study provides a systematic framework for predicting resource requirements, optimizing investment, and improving planning and supply chain management in India’s construction sector.
Planning Commission Perspective Planning Division
Keywords: Construction Planning; Material Requirements; Labour Norms; Building Projects; Road Construction; Expenditure Analysis; Resource Allocation; CPWD; Technical Ratios; Cost Estimation; Infrastructure Development; Standardization